#### Answer

$-64$

#### Work Step by Step

$(2i)^{6}=2^{6}\times i^{6}=64\times (i^{2})^{3}=64\times (-1)^{3}=-64$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$-64$

$(2i)^{6}=2^{6}\times i^{6}=64\times (i^{2})^{3}=64\times (-1)^{3}=-64$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.